Adaptive Capacity Mapping of Semarang Offshore Territory by the Increasing of Water Level and Climate Change - Suhelm, Ifan Ridlo (Forum Geografi, 2013)
Tidal inundation, flood and land subsidence are the problems faced by Semarang city related to climate change. Intergovernmental Panel on Climate Change (IPCC) predicted the increase of sea level rise 18-59 cm during 1990-2100 while the temperature increase 0,6Â°C to 4Â°C during the same period. The Semarang coastal city was highly vulnerable to sea level rise and it increased with two factors, topography and land subsidence. The purpose of this study was to map the adaptive capacity of coastal areas in the face of the threat of disasters caused by climate change. The parameters used are Network Number, Employee based educational background, Source Main Livelihoods, Health Facilities, and Infrastructure Road. Adaptive capacity of regions classified into 3 (three) classes, namely low, medium and high. The results of the study showed that most of the coastal area of Semarang have adaptive capacities ranging from low to moderate, while the village with low capacity totaling 58 villages (58.62%) of the total coastal district in the city of Semarang.